Photometric analysis of SW Lac short period binary star - Helen Zrar Hamad Ameen; Ismail Musa Murad (Zanco Journal of Pure and Applied Sciences, 2023)
In this research, the short period binary system named (SW Lac) have been chosen to be analyzed with U,B and V light curves with the PHOEBE program .The geometrical and physical parameters have been obtained and compared with previous results of papers. The present result indicated that the selected system is over contact also the absolute parameters have been obtained with suitable results as compared with previous results of previous papers. The O’Connel effect ratio have been obtained by using the methods of integration ,summation method also compared with the exact method the results of O’Connel effect ratio with integration method and summation methods are near with the result of difference in magnitude with exact method .The roche lobe radii and bolometric magnitude have been obtained with suitable results.